Vocabular Therapeutics - Sanjay Kalra; Sourabh Sharma; Rahul Chauda; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
In this communication, we introduce vocabular therapeutics, a novel aspect of health care. Vocabular therapeutics may be defined as the use of language models to assess, and address, internal impediments to healthy behaviour, based upon the choice of vocabulary of an individual (or society). The analysis of words, phrases and sentences, allows modification of “unhealthy” beliefs and choices, thus facilitating healthier behaviour. This is based upon the premise that thoughts, words and actions are able to influence each other, finally reaching a state of concordance. Vocabular therapeutics should be considered an integral part of behavioural therapy, lifestyle modification and medication counselling. The concept finds utility in chronic disease care, including obesity management. Keywords: Biopsychosocial, chronic disease, diabetes, communication, obesity, psychosocial.